A COMPARISON OF THE INTERACTION OF PRONOMINALS AND WORD ORDER IN NARO AND GǁANA - Letsholo, Rose; Saul, Isaac (Language matters (Pretoria, South Africa), 2015)
This article compares PGN markers, the pronoun system and word order in declaratives in Naro ǁGana. These languages are similar in that (a) nouns are marked for person, gender and number; (b) both have complex pronoun systems; (c) the plural and dual categories distinguish inclusive from exclusive pronouns; (d) main lexical items in both languages can be focused through fronting. They differ in that ǁGana NPs are marked for nominative and oblique case through the PGN marker, while in Naro this is not so. In Naro if constituents are re- ordered, the PGN marker of the fronted constituent hosts the PGN marker of the subject NP, thus identifying the subject. The use of pronouns in a sentence impacts word order at sentential level in Naro but not in ǁGana. PGN markers are obligatory for subjects only in ǁGana.